2010
DOI: 10.1007/s10688-010-0029-7
|View full text |Cite
|
Sign up to set email alerts
|

On optimal harmonic synthesis from inaccurate spectral data

Abstract: The problem of optimal recovery of derivatives of functions on the real line from inaccurate Fourier transforms of these functions on a finite interval is studied. Optimal recovery methods different in data handling procedures are constructed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…It turned out that in some cases it is possible to construct a whole family of optimal recovery methods for a linear operator. The study of such families began in [20] and continued in [21], [22], [14] and [19].…”
mentioning
confidence: 99%
“…It turned out that in some cases it is possible to construct a whole family of optimal recovery methods for a linear operator. The study of such families began in [20] and continued in [21], [22], [14] and [19].…”
mentioning
confidence: 99%
“…The problems of this kind are also considered in [3]. Based on the general principles of extremal problems the new approach can be found in [5,13,7,6], as well as some results in this area. In the papers [8,4] authors obtained some inequalities for derivatives and showed that the problem of finding the exact constants in such inequalities can be formulated and efficiently solved as the corresponding optimal recovery problem.…”
mentioning
confidence: 99%
“…Пусть ϕ a -такое отображение. Оценим квадрат максимизируемого функционала в (14) с ϕ = ϕ a , переходя по теореме Планшереля к образам Фурье (f (ξ) λ(A), если ξ ∈ R d \ A):…”
unclassified